Pilot project in rural western Madhya Pradesh, India, to assess the feasibility of using LED and solar-powered lanterns to remove kerosene lamps and related hazards from homes. Issue 3 (May 2015) - Chamania, S.; Chouhan, R.; Awasthi, A.; Bendell, R.; Marsden, N.; Gibson, J.; Whitaker, I.S.; Potokar, T.S.
Highlights We implemented strategies to reduce the risk of domestic burns in rural India. We replaced kerosene lamps with sustainable light sources in 1042 households. The lighting cost was reduced by 85% per year and was deemed socially acceptable. We successfully demonstrated a significant decrease in the use of kerosene lamps. Replacing kerosene lamps is a viable prevention strategy for reducing burns.